A comparative study of dipolarization fronts at MMS and Cluster. Issue 12 (25th June 2016) - Schmid, D.; Nakamura, R.; Volwerk, M.; Plaschke, F.; Narita, Y.; Baumjohann, W.; Magnes, W.; Fischer, D.; Eichelberger, H. U.; Torbert, R. B.; Russell, C. T.; Strangeway, R. J.; et al.
Abstract: We present a statistical study of dipolarization fronts (DFs), using magnetic field data from MMS and Cluster, at radial distances below 12 R E and 20 R E, respectively. Assuming that the DFs have a semicircular cross section and are propelled by the magnetic tension force, we used multispacecraft observations to determine the DF velocities. About three quarters of the DFs propagate earthward and about one quarter tailward. Generally, MMS is in a more dipolar magnetic field region and observes larger‐amplitude DFs than Cluster. The major findings obtained in this study are as follows: (1) At MMS ∼57 % of the DFs move faster than 150 km/s, while at Cluster only ∼35 %, indicating a variable flux transport rate inside the flow‐braking region. (2) Larger DF velocities correspond to higher B z  values directly ahead of the DFs. We interpret this as a snow plow‐like phenomenon, resulting from a higher magnetic flux pileup ahead of DFs with higher velocities. Key Points: MMS is generally located in a more dipolar magnetic field region and observes larger‐amplitude DFs than Cluster farther down the tail A larger fraction of DFs move faster closer to Earth, suggesting variable flux transport rates in the flow‐braking region Larger DF velocities correspond to a higher Bz directly ahead of DFs, suggesting a higher flux pileup ahead of DFs with higher velocities